2020
DOI: 10.2174/1574892815666200401113805
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib – First Therapeutic Proteasome Inhibitor for Cancer Therapy: A Review of Patent Literature

Abstract: Background: Bortezomib is reversible inhibitor of proteasome proteins for mammalian cells. Bortezomib is proven to be cytotoxic to a number of tumor cells by disrupting their normal homeostatic mechanism and thereby causing cell death. Currently, Bortezomib is prescribed for patients with multiple myeloma and mantle cell lymphoma. Objective: This assessment highlights the overview of recent patents of Bortezomib. This review includes patents grouped in sections like product patents, process patent, composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 3 publications
0
10
0
2
Order By: Relevance
“…Virtually all of our compound 1-resistant clones, with the exception of RES IV (2.5-fold resistant), demonstrated considerable cross-resistance to this established proteasome inhibitor (20- to 127-fold; Table 2 ). In addition, the broad-spectrum anti-kinetoplastid proteasome inhibitor GNF6702 ( 20 ) demonstrated similar levels of cross-resistance against RES I to V clones, while there was no evidence of cross-resistance to the classical proteasome inhibitor bortezomib, used in the treatment of multiple myeloma, mantle cell lymphoma, and a number of other cancers ( 23 ) ( Table 2 ). GNF6702, GSK3494245, and analogues are known to target the same allosteric binding site at the interface of the β4/β5 subunits of the proteasome resulting in the inhibition of chymotrypsin-like activity.…”
Section: Resultsmentioning
confidence: 99%
“…Virtually all of our compound 1-resistant clones, with the exception of RES IV (2.5-fold resistant), demonstrated considerable cross-resistance to this established proteasome inhibitor (20- to 127-fold; Table 2 ). In addition, the broad-spectrum anti-kinetoplastid proteasome inhibitor GNF6702 ( 20 ) demonstrated similar levels of cross-resistance against RES I to V clones, while there was no evidence of cross-resistance to the classical proteasome inhibitor bortezomib, used in the treatment of multiple myeloma, mantle cell lymphoma, and a number of other cancers ( 23 ) ( Table 2 ). GNF6702, GSK3494245, and analogues are known to target the same allosteric binding site at the interface of the β4/β5 subunits of the proteasome resulting in the inhibition of chymotrypsin-like activity.…”
Section: Resultsmentioning
confidence: 99%
“…Nelarabine is an effective anticancer chemotherapy prodrug of arabinfuranosylguanine triphosphate, that appears to meditate DNA degradation and cell death ( Robak et al, 2006 ). Similarly, midostaurin ( Hsiao et al, 2019 ), fluphenazine ( Otręba and Kośmider, 2021 ), bortezomib ( Vora et al, 2020 ), and vincristine ( Xu and Xu, 2020 ) also possess anticancer activity. The present findings revealed that GSDM gene expression may provide important guidance for the selection of targeted drugs for the treatment of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there has been much interest regarding the use of BZB, an original PI for other cancers therapy, such as rhabdomyosarcoma, HCC, malignant lymphoma, Hodgkin lymphoma, multiform glioblastoma, pancreatic cancer, bladder cancer, prostatic carcinoma, oophoroma, oesophageal cancer and leukaemia. The underlying mechanisms include inhibition of oncoproteins and induction of apoptosis, arrest of the cell cycle, suppression of EMT, reduction of stemness, stimulation of NK cell‐mediated immune response and inhibition of NF‐kappaB 22 . These mechanisms are somewhat dependent on its conventional proteasome inhibition.…”
Section: Discussionmentioning
confidence: 99%